A study of the optical properties of polypropylene based polymer composite films - Boydag, FS; Mamedov, SV; Alekperov, VA; Kandemir, G (WILEY-V C H VERLAG GMBH, 1999)
The optical clarity of the polymeric material can be influenced by changing the preparations parameters and thus the polymer structure. In this study, the transmittance, absorptance and reflectance of the polypropylene (PP) based polymer composites, synthesized by pressing method, changing the thickness between 8 - 29 mu m, are investigated. Infrared and ultraviolet spectra of PP/diamond and PP/fiber composite in the wavelength range 200-25000 nm are examined. Optical absorption spectra recorded in the UV-Visible range are presented; the determined values of energy gaps are listed. The results indicate that both mechanism, direct and indirect transitions may exist. The analysis of absorption peaks corresponding to oxygen groups, for PP/diamond (0.3-0.5 %) and PP/fiber (20-30 %) composites, show low optical densities which complies with our other studies.
Keywords: Polymer Science